The buy-write strategy, index investment and the efficient market hypothesis: more Australian evidence - O'Connell, Darren; O'Grady, Thomas (Barry) (School of Economics and Finance, Curtin Business School, 2009)
The purpose of this study is to examine the performance of an index buy-write strategy in the using three portfolios based on the Whaley (2002) approach; one for a portfolio of bank bills, one for a benchmark index and the third for a benchmark index hedged by index call options. The study uses Australian daily data between 1991 and 2006 and confirms that the buy-write strategy outperforms the index-only portfolio on both a risk and return basis. In addition, the strategy is seen to produce abnormal returns and therefore provides further evidence that appears to violate the efficient market hypothesis.